2022
DOI: 10.1371/journal.pone.0274001
|View full text |Cite
|
Sign up to set email alerts
|

Parents’/caregivers’ fears and concerns about their child’s epilepsy: A scoping review

Abstract: Background Childhood epilepsy is a serious and common neurological condition and can have life-long consequences and its impact can pervade all aspects of family life. Whilst the medical management of seizures is important, much of the day-to-day home management of epilepsy is invisible to people external to the family, including health care professionals, and parents’/caregivers’ fears and concerns can go unacknowledged and unaddressed by health care professionals. Objective This objective of this review wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 78 publications
1
6
0
Order By: Relevance
“…Worries about day-to-day living and future life of their persons were expressed by the participants. This finding has been reported in a scoping review where it was found that pervasive fear associated with the unexpected and uncertain nature of parenting a child with epilepsy exited among the caregivers [ 32 ]. The possible explanation is that managing the day-to-day care of a person with epilepsy can be exacerbated by the often unpredictable nature of the condition [ 33 ].…”
Section: Discussionsupporting
confidence: 55%
“…Worries about day-to-day living and future life of their persons were expressed by the participants. This finding has been reported in a scoping review where it was found that pervasive fear associated with the unexpected and uncertain nature of parenting a child with epilepsy exited among the caregivers [ 32 ]. The possible explanation is that managing the day-to-day care of a person with epilepsy can be exacerbated by the often unpredictable nature of the condition [ 33 ].…”
Section: Discussionsupporting
confidence: 55%
“…In addition, it complemented and enriched its analysis based on articles published in journals indexed in the JCR-WoS, with three articles on the same topic that were already included in a previous review that did not consider the first bibliometric technique indicated in the present methodological design. In this way, it was possible to incorporate six articles that covered five original empirical studies on telesupervision and that were evaluated with a tool (MMAT) that has been applied in several reviews related to health and mental health [ 72 , 73 , 74 ] among others.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to seizures, uncontrolled epilepsy can be associated with a loss of predictability for patients and caregivers that can result in fear and anxiety associated with concerns about such issues as prognosis, the future, and medication [ 15 ]. Anxiety may be associated with avoidance of activities to potentially avoid seizure clusters in a pathological condition that has been called anticipatory anxiety or seizure phobia [ 16 , 17 ].…”
Section: What Are Some Of the Consequences Of Unmanaged Seizure Clust...mentioning
confidence: 99%